Effect of Emotional Intelligence to Innovative Work Behavior of Employees Mediated with Tacit Knowledge Sharing in Education Department of Aceh - Riandy Oyadiwa (Jurnal Kawistara, 2022)
The purpose of research was to find out the effect of Emotional Intelligence (EI) to Innovative Work Behavior (IWB), and the mediating effect of Tacit Knowledge Sharing (TKS) to Emotional Intelligence (EI) and Innovative Work Behavior (IWB) of employee of the Education Department of Aceh. Using data from 100 employees from the Education Department of Aceh. Sampling was purposefully chosen within each level of office management. The independent variable in this research was Emotional Intelligence, while the dependent variable was Innovative Work Behavior and the mediating variable was Tacit Knowledge Sharing. The method approach is a quantitative method with data collection from questionnaires. The data is analyzed with SPSS program and further analyze with Path analysis method that had been tested for its instrument before validity test and reliability test. The finding of research showed that Emotional Intelligence is positively related to innovative work behavior. Emotional intelligence is positively related to tacit knowledge sharing, tacit knowledge sharing is positively related to innovative work behavior and tacit knowledge sharing mediates emotional intelligence and innovative work behavior